PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII.1 SMP NEGERI 2 PEKANBARU TAHUN PELAJARAN 2011/2012 - Darmawati '; Arnentis '; Henny Julianita Husny (Biogenesis, 2011)
Classroom Action Research has been conducted (PTK), which aims to improve the scientific attitude and learning outcomes with the implementation of IPA Biology cooperative learning model types Course Review Horay (CRH) in VIII.1 grade students at SMP Negeri 2 Pekanbaru. The study was conducted from October to November 2011. The study subjects were 36 students (17 male and 19 female). Parameter is the attitude of scientific research, the study (absorption and completeness of student learning), award groups, student activity and teacher activity (as the supporting data). Data were analyzed descriptively. The results indicate that the cycle I mean the scientific attitude of students is 82.25% (enough), the average absorption of students is 81.08 (enough), the thoroughness of student learning is 80.56% (enough) and group awards a super predicate there are 4 groups. In the second cycle the average scientific attitude of students increased to 90.99% (good), the average absorption of students is 89.61 (good), exhaustiveness of student learning is 100% (excellent) and a group award super predicate there are 2 groups. From the research results can be concluded that with the implementation of cooperative learning model of the type of course review horay (CRH) may increase the scientific attitude and learning outcomes VIII.1 grade Biology students of SMP Negeri 2 Pekanbaru Lessons Year 2011/2012Key words : Models of Cooperative Learning Type Course Review Horay (CRH), Scientific Attitudes, The Study of Biology